The use of technology in the learning environment for business communication: applied linguistics of business communication from the positive psychology perspective - Pikhart, Marcel (Procedia computer science, 2020)
The paper deals with implementation of a smart learning environment, namely Blackboard, into the course of business communication. The new approach was implemented into the course and the research was conducted into the subjective satisfaction of the users of the environment. The first research was conducted in 2018 into the users´ satisfaction with the course which was taught using traditional methods, and the second research was conducted in 2019 into the users´ satisfaction with the new online course. The idea of the creator of the online course was to keep the contents and the scope of the subject as much similar as possible to create two groups of users, i.e. the first, using the traditional approaches, and the second with the modern technology-enabled class. With this intention, the Blackboard class was created, and the users were taught by using blended learning methodology. The research focused merely on personal satisfaction with the course within the intention of positive psychology, i.e. focusing on potential issues regarding personal satisfaction. It did not focus on the differences in the performance of the students as there is a lot of research into this aspect. However, it focused on the individual satisfaction and personal feelings of the users while using blended learning platforms in the context of ubiquitous computing. The findings are that the users expressed their satisfaction regarding easily accessible materials and varied learning environment; however, the dissatisfaction was created by increased screen time and reduces social contacts. The findings are very important for educators who use various mobile platforms and eLearning environments as they should be aware of the reservations of the users of these tools.